Changes in lung function and respiratory symptoms during pesticide spraying season among male sprayers - Ratana Sapbamrer (2019)
© 2019, © 2019 Taylor & Francis Group, LLC. Exposure to pesticides via inhalation might impair lung function and develop further severe respiratory symptoms and diseases. Thus, the purpose of the study was to compare lung function between pre- and post-pesticide spraying seasons among male sprayers. The study also evaluated the association of lung function changes and other factors with respiratory symptoms. The follow-up study was conducted on 58 male sprayers. The subjects were interviewed and measured lung function before and after pesticide spraying season. The results found that forced vital capacity (FVC), forced expiratory volume in one second (FEV 1 ), and peak expiratory flow rate in the post-spraying season were significantly lower than in the pre-spraying season. With regard to respiratory symptoms, cough symptoms were associated with changes in FEV 1 /FVC [odd ratio (OR) = 1.29, 95% confidence interval (CI) = 1.01–1.67)] and smoking status (OR = 12.95, 95%CI = 1.35–124.34). Phlegm symptoms were also associated with changes in FVC (OR = 2.07, 95%CI = 1.01–4.25) and FEV 1 (OR = 0.41, 95%CI = 0.18–0.91). The study provides evidence that pesticide spraying may increase risks for significant alteration of lung function and respiratory symptoms.